STRUCTURE OF EXECUTIVE COMPENSATION PLAN OF LISTED COMPANIES IN BRAZIL - Souza, Paulo Vitor Souza de; Duque, Andréa Paula Osório; Silva Junior, Dércio Santiago da (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study aims to show the structure of the compensation plan of Brazilian companies, identifying whether the incentives offered to managers help to minimize the agency conflict between the parties. A well-structured compensation plan assists in the alignment of interests between principal and agent. The study is characterized as descriptive, documentary and qualitative. The forms of reference of 291 publicly traded companies that provided information regarding executive compensation were analyzed in the years 2011 to 2013. More than half of companies adopt only short-term pay and few companies provide postemployment compensation to its executives. These factors contribute to the executives maximize their own interests, damaging the interests of the principal in the long run. We conclude that the remuneration plans of public companies in Brazil facilitate the manipulation of information, taking into account many short-term remuneration and remuneration based on accounting numbers.